Actors’ contributions to the development of tourist attraction (Study in Nyalembeng, Central Java, Indonesia) - Desy Nur Aini Fajri; Rossa Estu Illahi (Borneo Novelty Publishing, 2025)
Purpose – This research administers an analysis of actors’ contribution to the development of a tourist attraction.Methodology/Design/Approach – A qualitative descriptive approach was invoked. Data were collected through interviews, observation, and documentation. Three informants were selected using a purposive sampling technique and under two criteria, which were (1) being knowledgeable and (2) having engaged in developing the intended tourist attraction since its establishment. Data analysis was carried out through three stages, i.e., data reduction, data presentation, and conclusion drawing. Findings – This research founded that three contributions actors made to developing the tourist attraction of Bukit Tangkeban in Nyalembeng, Central Java, Indonesia, namely (1) Human resource capacity building, (2) Unique tourist attraction packaging, and (3) Digital information technology utilization.Originality/value – As it is limited to Bukit Tangkeban in Nyalembeng, the results cannot act as generalizations applicable to other tourist destinations with different characteristics. This research provides insight into best practices concerning the development of a tourist attraction in a village in a developing country.